2010
DOI: 10.1039/b920794e
|View full text |Cite
|
Sign up to set email alerts
|

Direct multiple C–H bond arylation reaction of heteroarenes catalyzed by cationic palladium complex bearing 1,10-phenanthroline

Abstract: A cationic palladium complex bearing 1,10-phenanthroline ligand is found to catalyze direct C-H arylation reactions of heteroarenes with aryl iodides to give mono-, di-, or tri-arylated products selectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(57 citation statements)
references
References 41 publications
3
54
0
Order By: Relevance
“…The reaction of Zn II porphyrin 1-Zn (M = Zn) with 3,5-dimethylbromobenzene afforded none of the diarylated product and the corresponding monoarylated porphyrin in 33 % yield. [13,14] According to Fagnou and co-workers, [9f, 10a, 15] the most plausible mechanism for the arylation reaction consists of the following elementary steps (Scheme 1 a): 1) oxidative addition of an aryl bromide to Pd 0 to produce an arylpalladium bromide, 2) bromide-pivalate exchange to provide an arylpalladium pivalate, 3) CMD of the porphyrin with the arylpalladium pivalate to form an aryl(porphyrinyl)palladium, and 4) reductive elimination to result in arylation of the porphyrin and liberation of the initial Pd 0 complex. No conversion was observed in the reaction of free-base porphyrin 1-H 2 (M = 2H) because a palladium cation was captured by the substrate.…”
mentioning
confidence: 99%
“…The reaction of Zn II porphyrin 1-Zn (M = Zn) with 3,5-dimethylbromobenzene afforded none of the diarylated product and the corresponding monoarylated porphyrin in 33 % yield. [13,14] According to Fagnou and co-workers, [9f, 10a, 15] the most plausible mechanism for the arylation reaction consists of the following elementary steps (Scheme 1 a): 1) oxidative addition of an aryl bromide to Pd 0 to produce an arylpalladium bromide, 2) bromide-pivalate exchange to provide an arylpalladium pivalate, 3) CMD of the porphyrin with the arylpalladium pivalate to form an aryl(porphyrinyl)palladium, and 4) reductive elimination to result in arylation of the porphyrin and liberation of the initial Pd 0 complex. No conversion was observed in the reaction of free-base porphyrin 1-H 2 (M = 2H) because a palladium cation was captured by the substrate.…”
mentioning
confidence: 99%
“…[139] A year earlier, Shibahara and Murai had discovered that the cationic complex PdA C H T U N G T R E N N U N G (phen) 2 A C H T U N G T R E N N U N G (PF 6 ) 2 bearing the 1,10-phenanthroline ligand was able to catalyze the efficient bis-arylation of 1-methylpyrrole (44a) with a large molar excess of 4-trifluoromethyliodobenzene in DMA at 150 8C in the presence of Cs 2 CO 3 as the base (Scheme 108). [140] The reaction conditions shown in Scheme 107 were also found to be suitable for the 2,5-bis-arylation of thiophene, 3-methylthiophene and benzo[b]furan. [140] In 2009, Pellet-Rostaing, Lemaire and co-workers reported that the reaction of 8-oxo-5,5,7,8-tetrahydroindolizine (206) with 1.2 equiv.…”
Section: Scheme 101 a C H T U N G T R E N N U N G [Rucl 2 A C H T U mentioning
confidence: 94%
“…[140] The reaction conditions shown in Scheme 107 were also found to be suitable for the 2,5-bis-arylation of thiophene, 3-methylthiophene and benzo[b]furan. [140] In 2009, Pellet-Rostaing, Lemaire and co-workers reported that the reaction of 8-oxo-5,5,7,8-tetrahydroindolizine (206) with 1.2 equiv. of (hetero)aryl bromides in NMP at 100 8C in the presence of 2 equiv.…”
Section: Scheme 101 a C H T U N G T R E N N U N G [Rucl 2 A C H T U mentioning
confidence: 94%
“…11 However, a direct C–H bond arylation of imidazopyridine 1 is limited to a few examples of cationic Pd-catalyzed C-1 arylation of C-3-substituted imidazo[1,5- a ]pyridines. 12 To the best of our knowledge, there are no reports on a direct C-3 C–H arylation of 1 . Based on our previous regioselective Pd-catalyzed electrophilic arylation of indolizines, 13 we envisioned that the structural similarity of imidazo[1,5- a ]pyridine and indolizine might allow the same type of transformations to occur.…”
mentioning
confidence: 99%